'Time is prognosis' in heart failure: time‐to‐treatment initiation as a modifiable risk factor. (16th October 2021) - Abdin, Amr; Anker, Stefan D.; Butler, Javed; Coats, Andrew J. Stewart; Kindermann, Ingrid; Lainscak, Mitja; Lund, Lars H.; Metra, Marco; Mullens, Wilfried; Rosano, Giuseppe; Slawik, Jonathan; Wintrich, Jan; et al.
Abstract: In heart failure (HF), acute decompensation can occur quickly and unexpectedly because of worsening of chronic HF or to new‐onset HF diagnosed for the first time (' de novo '). Patients presenting with acute HF (AHF) have a poor prognosis comparable with those with acute myocardial infarction, and any delay of treatment initiation is associated with worse outcomes. Recent HF guidelines and recommendations have highlighted the importance of a timely diagnosis and immediate treatment for patients presenting with AHF to decrease disease progression and improve prognosis. However, based on the available data, there is still uncertainty regarding the optimal 'time‐to‐treatment' effect in AHF. Furthermore, the immediate post‐worsening HF period plays an important role in clinical outcomes in HF patients after hospitalization and is known as the 'vulnerable phase' characterized by high risk of readmission and early death. Early and intensive treatment for HF patients in the 'vulnerable phase' might be associated with lower rates of early readmission and mortality. Additionally, in the chronic stable HF outpatient, treatments are often delayed or not initiated when symptoms are stable, ignoring the risk for adverse outcomes such as sudden death. Consequently, there is a dire need to better identify HF patients during hospitalization and after discharge and treating them adequately to improve their prognosis. HF is an urgent clinical scenario along all its stages and disease conditions. Therefore, time plays a significant role throughout the entire patient's journey. Therapy should be optimized as soon as possible, because this is beneficial regardless of severity or duration of HF. Time lavished before treatment initiation is recognized as important modifiable risk factor in HF.